Flammability Performance of Intumescent Flame Retardant EPDM/PP-Based Thermoplastic Elastomers - Lu, Hongdian; Si, Jingyu; Zhao, Difang; Wu, Haotian; Ma, Yaqing; He, Hui (Asian Journal of Chemistry, 2012)
Flammability performance of intumescent flame retardant (IFR) ethylene-propylene-dieneterpolymer (EPDM)/polypropylene (PP) thermoplastic elastomers combined with montmorillonite (MMT) were evaluated using limiting oxygen index (LOI) and vertical combustion tests. The influences of montmorillonite on microstructure of the residual chars were studied by scanning electron microscope. The synergy between intumescent flame retardant and montmorillonite in improving flame retardancy of the materials has been found.